Immigration and the Reallocation of Work Health Risks - Osea Giuntella; Fabrizio Mazzonna; Catia Nicodemo; Carlos Vargas-Silva (Global Labor Organization (GLO), 2018)
This paper studies the effects of immigration on the allocation of occupational physical burden and work injury risks. Using data for England and Wales from the Labour Force Survey (2003-2013), we find that, on average, immigration leads to a reallocation of UK-born workers towards jobs characterized by lower physical burden and injury risk. The results also show important differences across skill groups. Immigration reduces the average physical burden of UK-born workers with medium levels of education, but has no significant effect on those with low levels. We also find that that immigration led to an improvement selfreported measures of native workers' health. These findings, together with the evidence that immigrants report lower injury rates than natives, suggest that the reallocation of tasks could reduce overall health care costs and the human and financial costs typically associated with workplace injuries.
Keywords: J61; I10; 330; Immigration; labor-market; physical burden; work-related injuries; health